The confinement of concrete in compression using CFRP composites – effective design equations - Benzaid, Riad; Mesbah, Habib-Abdelhak (Journal of Civil Engineering and Management, 2014)
This paper presents the results of an experimental study on the behaviour of axially loaded short concrete columns, with different cross sections that have been externally strengthened with carbon fibre-reinforced polymer (CFRP) sheets. Six series, forming the total of 60 specimens, were subjected to axial compression. All the test specimens were loaded to failure in axial compression and investigated in both axial and transverse directions. According to the obtained test results, FRP-confined specimen failure occurs before the FRP reached the ultimate strain capacities. Thus, the failure occurs prematurely and the circumferential failure strain is lower than the ultimate strain obtained from the standard tensile testing of the FRP composite. In existing models for FRP-confined concrete, it is commonly assumed that the FRP ruptures when the hoop stress in the FRP jacket reaches its tensile strength from either flat coupon tests, which is herein referred to as the FRP material tensile strength. This phenomenon considerably affects the accuracy of the existing models for FRP-confined concrete. On the basis of the effective lateral confining pressure of the composite jacket and the effective circumferential FRP failure strain, new equations were proposed to predict the strength of FRP-confined concrete and corresponding strain for each of the cross section geometry used, circular and square. The estimations given by these equations were compared with the experimental ones and general conclusions were drawn.